BSCI-17. Targeting SIRPα as a therapeutic strategy for the treatment of breast cancer brain metastasis. (9th August 2021) - Stirling, Elizabeth R; Bronson, Steven M; Crowe, William N; Wilson, Adam; Kooshki, Mitra; Zhao, Dawen; Triozzi, Pierre L; Lesser, Glenn J; Soto-Pantoja, David R
Abstract: Triple-negative breast cancer (TNBC) is a highly aggressive subtype of breast cancer characterized by the lack of druggable targets and an incidence of brain metastasis from the primary site of approximately 35%. There is no standard treatment for managing brain metastasis associated with TNBC; therefore, new strategies are urgently needed to overcome disease mortality. The CD47/SIRPα signaling pathway is implicated in tumor progression due to bypassing innate and adaptive immune surveillance. Most strategies targeting this pathway focus on targeting the receptor CD47; however, targeting SIRPα as a potential strategy to mitigate tumor burden remains understudied. Analysis of gene expression database shows that SIRPα expression is significantly elevated in invasive breast cancer when compared to primary. Furthermore, single-cell data indicates that SIRPα is expressed in basal epithelial cells in TNBC tumors aside from the myeloid compartment. Our immune staining against SIRPα in patient biopsies shows a five-fold increase in SIRPα expression in metastatic brain tumors compared to the primary lesions. Therefore, targeting SIRPα may be a new immunotherapeutic strategy to treat breast cancer brain metastases. Anti-SIRPα treatment of mice bearing brain metastatic 4T1br3 orthotopic tumors showed reduced tumor volume and tumor weight by over 50% compared to isotype control-treated mice. Furthermore, in a model of intracardial brain metastasis, treatment with SIRPα antibody was associated with a 60% increase in survival compared to isotype control-treated mice. RNA sequencing of tumors indicated that SIRPα blockade is associated with a reduction in genes linked to mitochondrial respiratory chain and increases in negative regulation of the cell cycle. Furthermore, in vitro SIRPα targeting enhanced the cell-mediated cytotoxicity of microglia against 4T1Br3 breast cancer cells. This suggests that SIRPα blockade may influence both tumor and innate immune cells to limit brain metastatic breast cancer growth and enhance survival.